2021
DOI: 10.1186/s40834-021-00152-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of intention to use postpartum intrauterine contraceptive device and associated factors among pregnant women attending antenatal clinics in ambo town public health institutions, Ethiopia, 2018

Abstract: Background Maternal mortality tragedy is the issue of both developed and developing countries, especially sub-Saharan Africa including Ethiopia, which is due to poor quality of maternal health care services. Therefore family planning especially the use of Postpartum intrauterine contraceptive devices can tackle unintended pregnancy and maternal death. However,the intention to use PPIUCD and the use of IUCD in general is not well practiced in Ethiopia according to evidences of the literatures. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
3
6
0
Order By: Relevance
“…Positive attitude towards PPIUCD was 48.7% in the study area. This finding is in line with the findings of a study done in Ambo town, Ethiopia (49.4%) [ 18 ]. The result of this study was higher than the study done in India (43.3%) [ 29 ], and in Tanzania(33.3%) [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Positive attitude towards PPIUCD was 48.7% in the study area. This finding is in line with the findings of a study done in Ambo town, Ethiopia (49.4%) [ 18 ]. The result of this study was higher than the study done in India (43.3%) [ 29 ], and in Tanzania(33.3%) [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…An intrauterine contraceptive device that can be inserted post placental, intra cesarean, and within 48 hours of delivery [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present review and meta-analysis, subgroup analysis was done by regions, study population, and study design indicated that there were variations in the utilisation of PPIUCD among different included regions, population and study design in Ethiopia. Accordingly, the highest in utilization of PPIUCD was observed in Addis Ababa 25.68% (95% CI: 11.07, 40.29) [ 27 , 32 34 ], 34.09% (95% CI: 32.52, 35.66) [ 32 , 35 ], and 21.63% (95% CI: 14.45, 28.81) [ 26 , 32 , 36 ] by region, study population and study design respectively. The observed differences could be due to culture, residence, educational status and religious differences across the region.…”
Section: Discussionmentioning
confidence: 99%